2021
DOI: 10.1002/anie.202110736
|View full text |Cite
|
Sign up to set email alerts
|

Hydroboration of Terminal Alkenes and trans‐1,2‐Diboration of Terminal Alkynes Catalyzed by a Manganese(I) Alkyl Complex

Abstract: A Mn I -catalyzed hydroboration of terminal alkenes Scheme 1. Overview of manganese-based hydroboration catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 67 publications
(11 reference statements)
0
29
0
Order By: Relevance
“… We also demonstrated that Mn­(I)–alkyl complexes are capable of activating C–H bonds of terminal alkynes converting aromatic and aliphatic terminal alkynes efficiently and selectively into head-to-head Z -1,3-enynes and head-to-tail gem-1,3-enynes . Most recently, we showed that Mn­(I)–alkyl complexes also catalyze the hydroboration of terminal alkenes (involving B–H bond activation) and the 1,2-diboration of terminal alkynes with pinacolborane (involving C–H bond activation) . Encouraged by these findings, we wondered if Si–H bonds may also be activated thereby initiating hydrosilylations and/or DS reactions of alkenes.…”
Section: Introductionmentioning
confidence: 89%
“… We also demonstrated that Mn­(I)–alkyl complexes are capable of activating C–H bonds of terminal alkynes converting aromatic and aliphatic terminal alkynes efficiently and selectively into head-to-head Z -1,3-enynes and head-to-tail gem-1,3-enynes . Most recently, we showed that Mn­(I)–alkyl complexes also catalyze the hydroboration of terminal alkenes (involving B–H bond activation) and the 1,2-diboration of terminal alkynes with pinacolborane (involving C–H bond activation) . Encouraged by these findings, we wondered if Si–H bonds may also be activated thereby initiating hydrosilylations and/or DS reactions of alkenes.…”
Section: Introductionmentioning
confidence: 89%
“… 2021 60 24488 24492 . 2 Efficient and selective anti-Markovnikow hydroboration of terminal alkenes by a manganese alkyl carbonyl complex was reported. Furthermore, fully acceptorless trans-1,2-diboration of terminal alkynes, including mechanistic investigations, was presented .…”
Section: Key Referencesmentioning
confidence: 99%
“…Remarkably, we observed high reactivity and selectivity in the anti-Markovnikov hydroboration of alkenes ( Scheme 14 ). 2 It should be noted that, thus far, only manganese complexes in the oxidation state of +II were utilized for hydroboration reactions of alkenes and alkynes by the groups of Zhang and Zheng, 36 Thomas, 37 Karton and de Ruiter, 38 and Rueping. 39 An array of terminal alkenes was efficiently hydroborated, tolerating a broad variety of functional groups such as halides, ethers, esters, and amines with a catalyst loading of merely 0.25 mol % Mn4 for most substrates.…”
Section: Hydrofunctionalization Reactionsmentioning
confidence: 99%
“…We have recently reported on the application of the Mn(I) alkyl complex fac -[Mn(dippe)(CO) 3 (CH 2 CH 2 CH 3 )] (dippe = 1,2-bis(di- iso -propylphosphino)ethane) ( Mn1 ) as precatalyst for the hydrogenation of ketones, 22 nitriles, 23 alkenes, 24 CO 2 , 25 the hydroboration and diboration of alkenes and alkynes, 26 the dehydrogenative silylation of alkenes, 27 and the dimerization and cross-coupling of terminal alkynes. 28 Inspired by these results, we wondered if Mn1 is also active in the semihydrogenation of alkynes.…”
Section: Introductionmentioning
confidence: 99%